PENYIMPANGAN PRINSIP KESANTUNAN PADA TEKS PENGUMUMAN KARYA SISWA KELAS VII SMP MUHAMMADIYAH 4 SAMBI TAHUN AJARAN 2015/2016: TINJAUAN PRAGMATIK - Wahyu Hartiningrum; Yunus Sulistyono (Universitas Muhammadiyah Surakarta, 2017)
This research has two aims as follow (1) to identify forms of deviation linguistic politeness in the text of announcements made by students of class VII SMP Muhammadiyah 4 Sambi (2) to describe the correct form of politeness to deviations linguistic politeness in the text of announcement made by students of VII grade SMP Muhammadiyah 4 Sambi. This research is a qualitative research. Objects of this research is a deviation politeness on the text of announcement made by students of VII grade. This research data such as words and sentences that contain the deviation politeness on the text of announcement made by students of VII grade SMP Muhammadiyah 4 Sambi. Data collection techniques are observe attentively methods and take notes, record and documentation. Authenticity technique of data in this research use triangulation technique. Data analysis techniques use padan intralingual method. This research results indicate that form of impoliteness speaking at announcement text made by students of VII grade SMP Muhammadiyah 4 Sambi Boyolali, include cost-benefit scale or of losses and gains scale, optionality scale, indirecness scale, authority scale, dan social distance. Impoliteness speaking on the text of announcement made by students in terms of optionality scale amounts to thirteen data. Impoliteness speaking on the text of announcement made by students in terms form authority scale amounts to one data.